Cyclical investment behavior across financial institutions - Yannick Timmer (Deutsche Bundesbank, 2016)
This paper examines the investment behavior in debt securities across financial institutions with a particular focus on how they respond to price changes. For identification, we use security-level data from the German Microdatabase Securities Holdings Statistics. Our results suggest that banks and investment funds may destabilize the market by responding in a pro-cyclical manner to price changes. For investment funds, this effect was even stronger during the crisis and periods of high uncertainty. Insurance companies and pension funds buy securities after a drop in prices. They also buy securities that are trading at a discount and sell securities that are trading at premium. This counter-cyclical behavior may stabilize markets whenever prices have been pushed away from fundamentals. Since our results suggest that institutions with impermanent balance sheet characteristics may exacerbate price dynamics, it is of crucial importance for financial stability to monitor the investor base as well as the balance sheets of both levered and non-levered investors.
Keywords: F32; G11; G15; G20; 330; Cyclicality; Portfolio Allocation; Financial Stability; Debt Capital Flows